RESPON PERTUMBUHAN DAN HASIL TANAMAN KAILAN TERHADAP PEMBERIAN KAPUR DOLOMIT DAN PUPUK BOKASHI KOTORAN SAPI DI TANAH GAMBUT - Melinda Yuniar; Hilda Susanti; Bambang Fredrickus (Universitas Lambung Mangkurat, 2021)
The study aimed to determine the response of growth and yield of kailan on the interaction effect of a dolomite lime with bokashi of cow manure and its single factor effect. The experiment was conducted in Completely Randomized Design (CRD) with two factors in three replications. The first factor was dolomite lime which consists of 2 t ha-1 (k1), 5 t ha-1 (k2), 10 t ha-1 (k3) and 15 t ha-1 (k4), while the second factor was bokashi of cow manure consisting of 0 t ha-1 (b0), 10 t ha-1 (b1), 15 t ha-1 (b2), and 20 t ha-1 (b3). By observing growth components consisting of relatif growth rate (RGR), crop growth rate (CGR), net assimilation rate (NAR), shoot/root ratio (S/R), and crop yield. As well as the components of soil nutrient content of N, P, K, C-organic content, pH and cation exchange capacity (CEC). The results showed that the application of dolomite lime at a dose of 15 t ha-1 with bokashi fertilizer at a dose of 20 t ha-1 give the highest value of crop growth rate (CGR), net assimilation rate (NAR), shoot/root ratio (S/R), C-organic content, phosphorus (P), and Potassium in peat soil. The application of bokashi fertilizer at a dose of 15 t ha-1 was not different with 20 t ha-1 in terms of relatif growth rate (RGR), crop yield and cation exchange capacity (CEC), and respectively higher than the dose of 10 t ha-1 and without bokashi fertilizer. The application of dolomite lime at a dose of 10 t ha-1 was not different with 15 t ha-1 on the relative growth rate (RGR), and pH of peat soil, and each dose was higher than the doses of 5 t ha-1 and 2 t ha-1 . In terms of nitrogen (N) content, the application of dolomite lime at a dose of 5 t ha-1 was not different with the dose of 10 t ha-1 , and 15 t ha-1 , the N content was higher than the dose of 2 t ha-1 . The increase in the dose of dolomite lime at 20 t ha-1 of bokashi fertilizer showed a positive linier correlation, except for the Potassium which showed a quadratic correlation. The increase dose of dolomite lime in the bokashi fertilizer, the plant growth rate (PAR), net assimilation rate (NAR), shoot/root ratio (S/R), C-organic content, and phosphorus (P) would increase as well. Each single factor of the dose of dolomite lime and bokashi fertilizer showed a positive linier relationship to the relatif growth rate (RGR), crop yield, N-total, pH, and cation exchange capacity (CEC) of peat soil, except for N-total and pH in bokashi fertilizer.